Freedom and Creativity from the Theater in Prison: Experience report of a theatrical practice with women in prison in the area of the forest of Minas Gerais (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This reflective account describes a theater teaching practicum carried out in the Performing Arts undergraduate course in the Arts Department of the Institute of Philosophy, Arts and Culture of the Federal University of Ouro Preto (DEART / IFAC / UFOP). It recounts the practice of a theater workshop with women prisoners and reflects on this work. It also analyzes the development of such a theatrical practice in the context of its audience.
Keywords: Theater; Prison; Theatrical Games